ANALISIS SISTEM DAN PROSEDUR PENCEGAHAN PENYALAHGUNAAN FAKTUR PAJAK DALAM UPAYA MENINGKATKAN PENGENDALIAN INTERN (Studi kasus pada KPP Pratama Surabaya Gubeng) - Surahmad, Nopan Anesta (Jurnal Mahasiswa Perpajakan, 2015)
Value Added Tax (VAT) has a significant and strategic role in the portion of the tax revenues. Tax receipts from the second largest VAT sector therefore income tax revenue. The main issues in the sector of VAT, is the amount of abuse the Tax Invoice. Tax Invoice is proof of payment of VAT on the purchase and delivery of goods and services. Purpose of this study was to analyze the sistem and procedures of the Directorate General of Taxation (DGT), which aims to prevent abuse of the Tax Invoice is set in the PER-24 / PJ/2012 and analyze Control internal Surabaya Gubeng.  This study used a qualitative descriptive approach. This study used data collection techniques such as interviews and documentation. The researchers in this study found that the sistems and procedures PER-24/PJ/2012 better sistem to tackle the problem because Fictitious Tax Invoice numbering sistem is controlled directly by the DGT to provide the serial number on the tax invoice to Taxable Person (PFM) which has been re-registered and verified by the DGT making it very difficult to perform misuse Tax Invoice.  The conclusion of this study is PER-24/PJ/2012  sistem is a good sistem to prevent abuse of the sistem Tax Invoice because is controlled directly by the DGT and Internal Control, which already meet the elements of the principles of good internal control.Keywords: System Analysis, Prevention, Misuse, Tax Invoice, Internal Control